Driving factors of vegetation cover change in Beibu Gulf Urban Agglomeration (Bangladesh Journal of Botany, 2025)
This study was based on remote sensing data from 2010 to 2023, and combined methods such as Geodetector to analyze the spatio-temporal variation characteristics and driving factors of the fractional vegetation cover (FVC) in the Beibu Gulf Urban Agglomeration. The study used the pixel dichotomy model to estimate the FVC, and evaluated the change trends through Theil-Sen trend analysis and Mann-Kendall significance test. The results showed that the FVC increased from 0.74 in 2010 to 0.80 in 2023, with an average annual growth rate of 0.0624/10/years. High-coverage areas are concentrated in Fangchenggang and Qinzhou in Guangxi, while low-coverage areas are mainly distributed in coastal cities such as Haikou and Zhanjiang. The analysis of driving factors shows that the urbanization rate (q-value = 0.6464) and precipitation (q-value = 0.5479) are the main influencing factors, and the interaction between population density and urbanization rate (q-value = 0.965) has the strongest explanatory power for vegetation cover. In the future, the change of vegetation cover will mainly be randomly stable. The persistent areas are mainly distributed in Chongzuo and the southern part of Nanning, while coastal cities such as Haikou and Zhanjiang may face the risk of degradation.Bangladesh J. Bot. 54(3): 711-719, 2025 (September) Special